(untitled) (University Arena, 2025)
Physical activity is a critical component of a healthy lifestyle, significantly contributing to the prevention and management of chronic diseases, mental health support, and overall well-being. Despite its benefits, recent lifestyle changes in post-communist Romania have led to an alarming increase in overweight and obesity rates, especially among urban youth. This research focuses on the University of Bucharest (UniBuc) to explore the reasons behind students’ low participation in university-organized physical activities. By employing a structured questionnaire distributed electronically, this study aims to collect comprehensive data on student demographics, participation levels, motivations, barriers, and suggestions for improvement. The quantitative analysis component of the study aims to identify participation trends and barriers, while qualitative insights will provide nuanced perspectives on students’ experiences. The findings will inform targeted strategies to promote physical activity among students, contributing to their immediate and long-term health. Overall, this exploratory study seeks to lay the groundwork for future research on enhancing physical activity participation in academic settings, ultimately supporting the holistic development of young adults.